EVALUASI JUMLAH PENGGUNAAN TRUK ANGKUTAN DI SUATU PERUSAHAAN HUTAN DI RIAU (An evaluation of the number of logging trucks used by a forest company in Riau) - Dulsalam Dulsalam (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
A study of the number of logging trucks used by a forest company in. Riau was carried out in 1989. To evaluate the number pf logging trucks, transport times and load. volumes of logging trucks were collected through a work time study. The objective is to find out the number of loggine trucks which meets the logging company's production target. The investigation comes up to the following conclusion:1.Log number and load volume averages hauled by Nissan TZ 52 logging trucks were 4 logs/trip and 23.84 m3 /trip, respectively. At the distance of 21 km, the logging trucks normally took 190.65 minutes (3.18 hours) to transport logs from the forest to log yard. Logging trucks could transport logs three round trips per day.2. The normal average productivity of the logging trucks was 71.52 m3 per day.3.The average productive time of logging trucks was 80% while the average non productive time was 20%.4. The number of logging trucks available was 2 units which conformed with the company's production target. For better operations: it is recommended that the company has one additional logging truck to meet its production target in the next working plan.